A Study on firm-level output growth, total factor productivity, and financial performance - KANG, Seok-Moo (KDI School, 2015)
Productivity is believed to be a key driver for a firm’s growth, especially for information and communication technology firms. This study calculated the total factor productivity growth of the major US ICT companies, and analyzed the relationship between the firms’ total factor productivity and output growth. This study also investigated the factors affecting the firm’s total factor productivity growth. The analysis shows that the selected firms’ output growth is positively affected by the firms’ capital input growth the most, followed by the firm’s total factor productivity growth. The firms’ total factor productivity growth is negatively affected by the cost factors. However, the factors affecting the individual firm’s total factor productivity growth are different across the firms. For example, in the case of Oracle, the firm’s total factor productivity is very positively affected by the technology innovation factor.
Thesis(Master) --KDI School:Master of Development Policy,2015